Low-dose decitabine enhances chidamide-induced apoptosis in adult acute lymphoblast leukemia, especially for p16-deleted patients through DNA damage. (August 2017) - Shi, Pengcheng; Zhang, Leisi; Chen, Kai; Jiang, Zhiwu; Deng, Manman; Zha, Jie; Guo, Xutao; Li, Peng; Xu, Bing
Aim: To investigate the combined action of decitabine (DAC) with chidamide (CS055) on acute lymphoblastic leukemia (ALL) cells.Materials & methods: ALL cell lines as well as primary cells from 17 ALL patients were subjected to different treatments and thereafter cell counting Kit-8 (CCK-8) assay, flow cytometry and western blot were employed to determine IC50, apoptosis and checkpoint kinase 1 and γH2A.X expression.Results: Low-dose DAC combined with CS055 could effectively kill ALL cells by the reduction of cell viability and induction of apoptosis. This was also observed in primary cells from 17 ALL patients, especially for those with p16 gene deletion. Suppression of checkpoint kinase 1 phosphorylation and upregulation of γH2A.X expression was demonstrated to participate in DAC plus CS055-induced apoptosis.Conclusion: Low-dose DAC could enhance chidamide-induced apoptosis in adult ALL, especially for patients with p16 gene deletion through DNA damage.